ULTRASONOGRAPHIC CHARACTERISTICS AND COMPARING WITH FINE-NEEDLE ASPIRATION CYTOLOGY RESULTS OF SUBACUTE GRANULOMATOUS (DE QUERVAIN’S) THYROIDITIS CASES - Nguyễn , Thị Thu Hằng; Lại, Thu Hương; Lê, Văn Khảng (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2024)
Purpose: To describe the ultrasound imaging characteristics of subacute thyroiditis and compare them to fine needle aspiration thyroid cytology results. Materials and methods: A retrospective and prospective cross-sectional descriptive study on patients diagnosed with subacute thyroiditis, who underwent ultrasound, and had fine–needle aspiration results at the Radiology Center, Bach Mai Hospital from January 2020 to April 2023. Results: The study was conducted on 65 patients with fine needle aspiration results as subacute thyroiditis, 90.8% female, and 63.1% in middle age (40 to 60 years old). Clinical symptoms including neck pain, low-grade fever, and increased metabolism were observed in 63.1% of cases. 67.7% of cases had heterogeneous hypoechoic lesions, with illdefined margins. In 45 cases Doppler color ultrasound was performed, 44 cases (66.2%) hypovascularity, and only 1 case (1.5%) hypervascularity. 35.4% of cases had hypoechoic thyroid nodules, of which 10.8% were classified as TIRADS 4 and 24.6% were classified as TIRADS 5. Conclusion: Subacute thyroiditis can present as hypoechoic nodules, which can easily be confused with malignancies, challenging in differential diagnosis. Fine-needle aspiration thyroid cytology is an essential procedure in atypical cases. Clinical coordination with imaging and cytology will help achieve an accurate diagnosis.